Spatiotemporal assembly and functional composition of planktonic microeukaryotic communities along productivity gradients in a subtropical lake - Zou, Songbao; Lian, Qingping; Ni, Meng; Zhou, Dan; Liu, Mei; Zhang, Xin; Chen, Guangmei; Yuan, Julin (Frontiers in Microbiology, 2024)
Microeukaryotes play crucial roles in the microbial loop of freshwater ecosystems, functioning both as primary producers and bacterivorous consumers. However, understanding the assembly of microeukaryotic communities and their functional composition in freshwater lake ecosystems across diverse environmental gradients remains limited. Here, we utilized amplicon sequencing of 18S rRNA gene and multivariate statistical analyses to examine the spatiotemporal and biogeographical patterns of microeukaryotes in water columns (at depths of 0.5, 5, and 10m) within a subtropical lake in eastern China, covering a 40-km distance during spring and autumn of 2022. Our results revealed that complex and diverse microeukaryotic communities were dominated by Chlorophyta (mainly Chlorophyceae), Fungi, Alveolata, Stramenopiles, and Cryptophyta lineages. Species richness was higher in autumn than in spring, forming significant hump-shaped relationships with chlorophyll a concentration (Chl-a, an indicator of phytoplankton biomass). Microeukaryotic communities exhibited significant seasonality and distance-decay patterns. By contrast, the effect of vertical depth was negligible.Stochastic processes mainly influenced the assembly of microeukaryotic communities, explaining 63%, 67%, and 55% of community variation for spring, autumn, and both seasons combined, respectively. Trait-based functional analysis revealed the prevalence of heterotrophic and phototrophic microeukaryotic plankton with a trade-off along N:P ratio, Chl-a, and dissolved oxygen (DO) gradients. Similarly, the mixotrophic proportions were significantly and positively correlated with Chl-a and DO concentrations. Overall, our findings may provide useful insights into the assembly patterns of microeukaryotes in lake ecosystem and how their functions respond to environmental changes.